The Characteristics of Suicide in Gunungkidul Indonesia - F A Nurdiyanto; Siti Jaroah (Disease Prevention and Public Health Journal, 2020)
Background: The suicide incidents in Gunungkidul did not decrease according to previous reports. This research was conducted to described suicide trends in Gunungkidul from 2012 to 2019 and their characteristics. Method: The research used retrospective approach by analyzing suicide data from local police based on demography (sex, occupation, age, residence) and the methods of suicide. We analyzed the suicide trends in the last 8 years. Results: The result of the descriptive analysis shows that suicide in Gunungkidul has the following characteristics: 1) mostly done by male than female, 2) farmers, 3) elderly (>60 years old) and adults (36-60 years old), and 4) hanging as the popular method to completed suicide. Conclusion: This research suggests that suicide prevention should be done to people with suicide risks, especially the elderly, and promotes suicide prevention to society. We proposed implementing community-based to reduce the accessibility of lethal methods of suicide.